Sub-debt yield spreads as bank risk measures - Douglas D. Evanoff; Larry D. Wall (Federal Reserve Bank of Atlanta, 2001)
Several recent studies have recommended greater reliance on subordinated debt as a tool to discipline bank risk taking. Some of these proposals recommend using sub-debt yield spreads as triggers for supervisory discipline under prompt corrective action (PCA). Currently such action is prompted by capital adequacy measures. This paper provides the first empirical analysis of the relative accuracy of various capital ratios and sub-debt spreads in predicting bank condition, measured as subsequent CAMEL or BOPEC ratings. The results suggest that some of the capital ratios, including the summary measure used to trigger PCA, have almost no predictive power. Sub-debt yield spreads performed slightly better than the best capital measure, the Tier-1 leverage ratio, albeit the difference is not significant. The performance of sub-debt yields satisfies an important prerequisite for using sub-debt as a PCA trigger. However, the prediction errors are relatively high and further work to refine the measures would be desirable.
Keywords: 330; Risk; Debt; Bank supervision; Bank capital